An nusual ocular manifestation of multiple myeloma. Issue 7 (22nd July 2022) - McGrath, Robert; Whitlow, Shane; McCabe, Grace Anne; McElnea, Elizabeth Margaret
Abstract : A man in his 70s with a history of multiple myeloma presented with a 4-day history of right ptosis and a rapidly enlarging upper eyelid mass. On examination, a large, firm, smooth, pink lesion was found to descend from the conjunctiva of the superior fornix. The patient underwent excision biopsy. Histopathological analysis demonstrated monoclonal plasma cells expressing light-chain kappa, consistent with extramedullary plasmacytoma. Clinical ophthalmic manifestations of multiple myeloma are rare but also diverse. Ocular surface manifestations of multiple myeloma are extremely uncommon. Variable examination findings mean those involving the conjunctiva and may be particularly challenging to diagnose. Secondary ocular extramedullary plasmacytoma, despite its rarity, should be considered in patients with multiple myeloma.